Learning and Teaching with ICT Resources: Innovating Experiences in University Faculty Education - Canales García, Alba (2020)
This paper describes the theoretical foundation developed by the authors in the use of information and communication technology (or technologies) (ICT) in the field of teacher education at División de Educología (DE), Centro de Investigación y Docencia, Universidad Nacional de Costa Rica (UNA), Omar Dengo Campus in Heredia. Based on several data gathered from the faculty, the authors identified different ICT needs they have. In this process, they wanted to evaluate the importance of implementing technological tools in the process of university faculty training and identifying the ICT demands the school has in order to propose different tools to improve the learning process in each given course. The results were obtained by considering the following ICT sources: blog, web browsers, Moodle-based learning platforms, videos, databases, social networks and Google Drive cloud storage tools. Also, this paper takes motivation, discovering, and maintaining the interest of students in guiding and informing as the main pedagogical purposes of the use of ICT.